2008
DOI: 10.1111/j.1468-2478.2007.00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Shame on You: The Impact of Human Rights Criticism on Political Repression in Latin America

Abstract: The most commonly used weapon in the arsenal of human rights proponents is shaming the violating government through public criticism. But does this really affect the behavior of the violator? This study examines how governments that are targeted for human rights criticism respond to subsequent contentious challenges. Analyzing 873 challenges in seven Latin American countries between 1981 and 1995, it is found that human rights criticism does lead governments to reduce repression of subsequent challenges in cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
119
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(127 citation statements)
references
References 53 publications
3
119
0
5
Order By: Relevance
“…A growing body of scholarship has demonstrated that human rights INGO shaming advocacy has, at least under certain conditions, had a significant impact on curbing the government's willingness to commit repression against it citizens (Hawkins 2002;Cardenas 2007;Franklin 2008;Fábián 2010;Murdie and Davis 2012;Smith-Cannoy 2012). Further work by Krain (2012) and DeMeritt (2012) find that shaming can be effective at stopping state-sanctioned systematic violence, such as mass killings and genocide.…”
mentioning
confidence: 98%
“…A growing body of scholarship has demonstrated that human rights INGO shaming advocacy has, at least under certain conditions, had a significant impact on curbing the government's willingness to commit repression against it citizens (Hawkins 2002;Cardenas 2007;Franklin 2008;Fábián 2010;Murdie and Davis 2012;Smith-Cannoy 2012). Further work by Krain (2012) and DeMeritt (2012) find that shaming can be effective at stopping state-sanctioned systematic violence, such as mass killings and genocide.…”
mentioning
confidence: 98%
“…Often, however, as was the case after September 11 th , states retain a quite influential position in their ability to articulate affect as emotion -to name that which citizens 'felt'. This is certainly not always the case, and many important examples exist of states failing to articulate their preferred policies to resonate affectively, and where NGOs 'shame' states to pursue a political agenda that they likely would not have pursued otherwise (Franklin, 2008). Frequently though, as was the case after 9/11 and as tends to follow perceived 'crisis situations', affect is often what states make of it.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Simmons (2000) analyzed states that were new entrants on the international scene, emerging from either a period of nondemocracy or global isolation and found that states were concerned with their reputations for respecting the rule of law because this affected the level of economic integration they were able to achieve. In addition, the power of shame which comes from a bad reputation has been found to be a strong deterrent for states, preventing them from engaging in norm-violating behavior (Donnelly 1998;Franklin 2008;Lebovic and Voeten 2006).…”
Section: A Theory Of Compliance and Reputationmentioning
confidence: 98%